Phage-Displayed T-Cell Epitope Grafted into Immunoglobulin Heavy-Chain Complementarity-Determining Regions: an Effective Vaccine Design Tested in Murine Cysticercosis - Manoutcharian, Karen (American Society for Microbiology, 1999)
A new type of immunogenic molecule was engineered by replacing all three complementarity-determining-region (CDR) loops of the human immunoglobulin (Ig) heavy-chain variable (V(H)) domain with the Taenia crassiceps epitope PT1 (PPPVDYLYQT) and by displaying this construct on the surfaces of M13 bacteriophage. When BALB/c mice were immunized with such phage particles (PIgphage), a strong protection against challenge infection in very susceptible female hosts was obtained. When specifically stimulated, the in vivo-primed CD4(+) and CD8(+) T cells isolated from mice immunized with PT1, both as a free peptide and as the PIgphage construct, proliferated in vitro, indicating efficient epitope presentation by both major histocompatibility complex class II and class I molecules in the specifically antigen-pulsed macrophages used as antigen-presenting cells. These data demonstrate the immunogenic potential of recombinant phage particles displaying CDR epitope-grafted Ig V(H) domains and establish an alternative approach to the design of an effective subunit vaccine for prevention of cysticercosis. The key advantage of this type of immunogen is that no adjuvant is required for its application. The proposed strategy for immunogen construction is potentially suitable for use in any host-pathogen interaction.